2016
DOI: 10.1016/j.yjmcc.2016.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D controls resistance artery function through regulation of perivascular adipose tissue hypoxia and inflammation

Abstract: Vitamin D deficiency in human subjects is associated with hypertension, metabolic syndrome and related risk factors of cardiovascular diseases. Serum 25-hydroxyvitamin D levels correlate inversely with adiposity in obese and lean individuals. Bioactive vitamin D, or calcitriol, exerts anti-inflammatory effects on adipocytes, preadipocytes and macrophages in vitro. We tested the hypothesis that vitamin D deficiency alters the phenotype of perivascular adipose tissue (PVAT) leading to impaired function in resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Perivascular adipose tissue (PVAT) in obesity produces factors that affect atherogenesis and smooth muscle cell proliferation, thereby affecting the contractile function. Pelham et al [98] demonstrated an association between vitamin D deficiency, impaired normal ability of PVAT to suppress contractile responses of the underlying mesenteric resistance artery to angiotensin II and serotonin, and enhanced angiotensin II-induced vasoconstriction. Vitamin D deficiency was also associated with the increased expression of TNF-α and heat-induced factor-1 alpha (HIF-1α).…”
Section: Vascular Diseasementioning
confidence: 99%
“…Perivascular adipose tissue (PVAT) in obesity produces factors that affect atherogenesis and smooth muscle cell proliferation, thereby affecting the contractile function. Pelham et al [98] demonstrated an association between vitamin D deficiency, impaired normal ability of PVAT to suppress contractile responses of the underlying mesenteric resistance artery to angiotensin II and serotonin, and enhanced angiotensin II-induced vasoconstriction. Vitamin D deficiency was also associated with the increased expression of TNF-α and heat-induced factor-1 alpha (HIF-1α).…”
Section: Vascular Diseasementioning
confidence: 99%
“…Previous reports have shown that 25(OH)D is associated with inflammation and may involve in the pathogenesis of PD . Although both Klt and 25(OH)D are correlated with neuroinflammation and age‐related diseases, the association of Klt and 25(OH)D with MSA severity has not been systemically elucidated. Homocysteine (Hcy) is a key product at the intersection of cysteine and methionine and is associated with neuroinflammation and cognitive dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Klt, 25(OH)D and Hcy are not only associated with inflammation and oxidative stress but also play important roles in the pathogenesis of various neurodegenerative diseases . To our knowledge, the independent and combined effects of Klt, 25(OH)D and Hcy have not been investigated in assessing MSA patients yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perivascular adipose tissue (PVAT) has been recently demonstrated to be a highly active endocrine organ, producing and releasing a variety of bioactive substances. [1][2][3] The most important role of PVAT is to reduce vasoconstrictive responses to noradrenaline or phenylephrine (PHE) by releasing various relaxation factors; this is called an anti-contractile property. 4 However, in obesity there are structural and functional changes in PVAT, which can result in vascular dysfunction by influencing endothelial and smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%